Stimulation of Children’s Cognitive: Development of Ulok Tangga Tolu Media Dimensions Based on Batak Culture - Malini, Ulfa; Heldanita, Heldanita; Salmiah, Salmiah; Rahmat, Zetri; Salina bt Samaun, Siti; Royahani, Farida; Irawan, Yossy (Aulad: Journal on Early Childhood, 2026)
This study addresses the lack of cultural recognition for children and limited educational game tools. It aims to develop a Batak culture-based three- dimensional ulak tangga tolu as an educational game to stimulate cognitive development in early childhood and assess its feastibility. The research employed a Research and Development (R&D) method using the ADDIE model, with data collected through questionnaires, observations, and documentation. Feasibility assessment from material experts, media experts, and teachers yielded percentages of 84.3%, 90.6%, and 91.18%, respectively, categorized as "very feasible." The trial with children showed a result of 94.01%. These findings indicate that the three-dimensional ulok tangga tolu is highly feasible and effective as a learning medium to enhance cognitive abilities in children aged 5-6 years.